Impacts of gender-inclusive extension approaches on farmer understanding and willingness to pay for bundled financial services - Timu, Anne G.; Manoti, Dismas; Shee, Apurba; You, Liangzhi (Elsevier, 2024)
Building the resilience of smallholder farmers, and their ability to cope with the negative impacts of climate shocks can significantly improve the sustainability of agriculture as a reliable source of livelihood. While innovations such as index insurance and bundled financial instruments could enhance smallholder farmers' climate resilience, their uptake, and use remain low, especially among women farmers. Based on experimental data from a risk contingent credit (RCC—an insurance bundled credit product) project in Kenya, we argue that employing inclusive extension approaches that address social inequities in information access and use could enhance gender equality in product understanding, a key determinant of uptake. We evaluate the gender differences of the impacts of conventional face-to-face, animated brochures, and video-based extension approaches on product understanding and willingness to pay (WTP) for RCC. We find that; (i) providing animated brochures to a random subset of farmers significantly improved their understanding and WTP for the product, (ii) the use of animated videos significantly increased product understanding, but it had weaker impacts on the farmers' WTP, and (iii) the impact of animated brochures on product understanding was significantly larger among women farmers. This study underscores the importance of addressing social and cultural barriers to agricultural information access and use, and designing tailored extension approaches to support men and women in making informed decisions about climate risk management. From a policy perspective, we conclude that addressing these barriers could foster a socially fair, and a more sustainable and resilient agricultural sector for both men and women smallholder farmers.